1982
DOI: 10.1016/0028-2243(82)90049-1
|View full text |Cite
|
Sign up to set email alerts
|

The relative contribution of different maternal factors in large-for-gestational-age pregnancies

Abstract: Relative and attributable risks were calculated to assess the potency of different maternal factors associated with large-for-gestational age (LGA) babies in individuals and in the population as a whole. In multiparous women the most important factor was the fast fetal growth rate demonstrated in previous pregnancies. Non-smoking also made a large contribution to the LGA population (43.65%) and the risk to individual patients was doubled. The relative risk for height steadily rose with increasing stature, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…A number of studies have shown a relationship between body habitus and birth weight (18)(19)(20)(21). Maternal adiposity (BMI) and maternal weight gain both correlated with infant adiposity for both GDM and control pregnancies, supporting our first hypothesis.…”
Section: Results-a Total Of 119 Mothersmentioning
confidence: 99%
“…A number of studies have shown a relationship between body habitus and birth weight (18)(19)(20)(21). Maternal adiposity (BMI) and maternal weight gain both correlated with infant adiposity for both GDM and control pregnancies, supporting our first hypothesis.…”
Section: Results-a Total Of 119 Mothersmentioning
confidence: 99%
“…C O N C L U S I O N S -A number of investigators have established the significance of maternal anthropometric status on newborn macrosomia (28)(29)(30)(31)(32). The followup anthropometric data in the current study supported our hypothesis that LGA IGDMs have increased central adiposity, including increased abdominal skinfold thickness and waist circumference at age 1 year, compared with all three study groups.…”
Section: Research Design a N D Methods-mentioning
confidence: 99%
“…Maternal height and body mass index have significant independent effects on birth weight. 6 7 Campbell et al reported that birth weight is not normally distributed at each week of gestation and that standardisation for parity, gestation, and sex of the baby is essential in any study looking at long term effects of differences in fetal growth. 8 This procedure controls for factors that can predetermine the weight of a baby, independent of an adverse fetal environment.…”
mentioning
confidence: 99%